Selective progesterone receptor modulators for the medical treatment of uterine fibroids with a focus on ulipristal acetate - Rabe, Thomas; Wallwiener, Markus (BioMed research international, 2018)
Uterine fibroids are the most frequent benign tumours in women of child-bearing age. Their symptoms are diverse and the quality of life of the women affected can be significantly impaired. While treatment to date has been primarily by means of surgical intervention, selective progesterone receptor modulators (SPRMs) open up new medication-based treatment options. EMA’s Pharmacovigilance Risk Assessment Committee (PRAC) has recently completed its review of ESMYA® (ulipristal acetate, 5 mg), following reports of serious liver injury, including liver failure leading to transplantation in postmarketing settings. We will provide some information on the PRAC’s recommendations to minimize this risk. Nevertheless, the effectiveness and safety of the SPRM ulipristal acetate (UPA), both with regard to preoperative administration and with regard to an intermittent administration as long-term treatment for patients with symptomatic uterine fibroids, have been shown in several clinical studies (PEARL I–IV).
Gesehen am 18.05.2020